Comparison of antiplatelet antibody profiles between hepatitis C virus-associated immune thrombocytopenia and primary immune thrombocytopenia. (17th November 2021) - Huang, Cih-En; Chen, Wei-Ming; Wu, Yu-Ying; Shen, Chien-Heng; Hsu, Chia-Chen; Li, Chian-Pei; Chen, Min-Chi; Chang, Jung-Jung; Chen, Yi-Yang; Lu, Chang-Hsien; Shi, Chung-Sheng; Chen, Chih-Cheng
Abstract: Hepatitis C virus-associated immune thrombocytopenia (HCV-ITP) has been assumed to be one of secondary ITP and associated with antiplatelet antibodies. This study was to clarify the antibody profile in HCV-ITP compared with primary ITP. We enrolled 55 HCV-ITP, 30 primary ITP, 11 Helicobacter pylori -ITP, 21 HCV control, and 16 healthy volunteers. We reviewed their blood cell counts, autoimmune markers, and spleen size. We used enzyme-linked immunosorbent assay kit to detect the specific antibody to glycoproteins IIb/IIIa, Ia/IIa, Ib/IX, IV, and human leukocyte antigen (HLA) class I. Compared with primary ITP patients, HCV-ITP patients had an older age, lower white blood cell (WBC) count and fewer presented with severe thrombocytopenia. The rate of positive antibody detection was 63.6% for the HCV-ITP group higher than the rate of 40% for the primary ITP. In the HCV control, antiplatelet antibodies were detected in 38.1% patients and no one had more than two types of antibodies. The antiplatelet antibodies correlated to severer thrombocytopenia. An HLA class I antibody was associated with lower WBCs and larger spleen. In conclusion, HCV-ITP patients had a high rate of positive antiplatelet antibody. The antibodies were associated with not only lower platelets but also leukopenia and splenomegaly.